PENGARUH SELEKSI KARYAWAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT BOGA INDO SEJATERA ABADI (PEPPER LUNCH) MEDAN - Kornelius Aperianus Bawamenewi; Novi Heldarnia Zalukhu; Riandi Andika Nababan (JURNAL ILMIAH SOCIO SECRETUM, 2021)
Resource development is carried out in the efforts to develop the quality or capability of resources, in order to be able to process and manage natural resources. It is hoped it can be used for community welfare as the ultimate goal of development itself. The population in this study was 30 people. The sample used was 98 people. The approaches applied were quantitative approach, quantitative descriptive research, descriptive explanatory research and multiple linear regression analysis. The results showed that simultaneous selection and training had a positive and significant effect on employees’ performance (21,032> 2,31) with a significant level of 0,000 <0,05). Partially the selection had positive and significant effect on employees’ performance (value calculated> t table (2.707> 1.66055) and a significant value> of 0.05). Partially the training had positive and significant effect on employees’ performance (value calculated> t table (5.054> 1.66055) and significant value> of 0.05).